Case Report: Microscope-assisted surgery of C7 nerve root cyst with neurological symptoms - Hao, Shenshen; Li, Hongke; Liu, Shuai; Guo, Yating; Chen, Honglei; Zhang, Zhifang; Dong, Shengli (Frontiers in Surgery, 2022)
Background Cervical nerve root cysts are rare and easily missed or misdiagnosed in clinical practice. Although conventional surgery is effective for cervical nerve root cysts, it is limited by the small surgical field of view and operating range, relatively difficult procedure, and incomplete cyst resection. Microscope-assisted magnification of the surgical field of vision reduces the difficulty and ensures complete cyst resection. Case presentation A 58-year-old male patient was diagnosed with a cervical nerve root sleeve cyst on the right C7 vertebra with neurological symptoms. Microscope-assisted surgery was used as treatment. The cyst was completely removed by the microscope-assisted surgery, with satisfactory patient recovery. The surgery did not produce complications, such as spinal cord neurovascular injury, and the patient's symptoms disappeared quickly after surgery. During the 2-year follow-up, there was no complication and no recurrence. Conclusion Microscope-assisted surgery in treatment of the C7 nerve root cyst could achieve a complete resection.